Project Stella and the impacts of fintech on financial infrastructures in Japan - Michinobu Kishi (Asian Development Bank Institute (ADBI), 2019)
Project Stella studies the possible use of distributed ledger technology (DLT) on financial market infrastructures (FMIs). DLT solutions have the potential to improve the safety and efficiency of existing systems, as shown by research undertaken by central banks and FMIs. Yet, balancing performance and network size with the distance between nodes, as in the case of Stella phase 1, or the flexibility of cross-ledger delivery-versus-payment (DVP) using hashed timelock contracts without connection between ledgers and liquidity efficiency, as in the case of phase 2, remains a challenge. Project Stella studies the possible use of DLT for FMIs, including large-value central bank RTGS systems. Phase 1 implemented the processing logic of the standard liquidity-saving mechanisms in a DLT environment, and the analysis found that an application could meet the performance needs of an RTGS system. There is a trade-off between DLT performance and network size or distance between nodes. DLT solutions have the potential to strengthen resiliency and reliability. In phase 2, the project team proved that cross-ledger DVP could function even without any connection between individual ledgers. Hashed timelock contracts and digital signatures would be used to achieve interoperability between ledgers, while liquidity efficiency and settlement speed may be negatively affected as a result. DLT solutions have the potential to improve safety and efficiency of existing systems adopted at FMIs, yet balancing diverse system requirements demands careful analysis and consideration. As shown by increasing research and proofs-of-concept on DLT undertaken by many central banks1 and securities exchanges in major jurisdictions, there are both opportunities and challenges for further exploration.
Keywords: G2; G15; F65; O16; 330; distributed ledger technology; financial market infrastructure; information technology innovation